Green Synthesis of Gold Nanoparticles Using Aronia Melanocarpa and their Interaction with Melanin - Dedecengiz Varol, Guleycan; Onder, Sakip; Gurel Pekozer, Gorke (SPRINGER HEIDELBERG, 2026)
PurposeGold nanoparticles (AuNPs) have attracted significant attention in biomedical research due to their unique optical and electronic properties, making them suitable for biosensing, drug delivery, and imaging applications. This study explores the green synthesis of AuNPs using Aronia melanocarpa, a fruit rich in polyphenols and anthocyanins, which has not been previously reported in the literature for gold nanoparticle synthesis. Given that melanin is a critical biomarker for melanoma progression, we investigated the interaction between melanin and AuNPs synthesized with green chemistry methods.MethodsAuNPs were synthesized using aronia extract as reducing/stabilizing agent. The interaction between AuNPs and melanin was investigated using UV-Visible (UV-VIS) spectrophotometry and fourier transform infrared spectroscopy (FTIR) to assess their potential applications in bioanalysis.ResultsThe study confirms the interaction of AuNPs with melanin which is a pigment with a high potential to be used in biomedical applications including melanoma detection and biosensors. Changes in absorbance and spectral shifts suggest a strong interaction between melanin and AuNPs, particularly in acidic environments, indicating potential for use in diagnostic or sensing applications.ConclusionThis research demonstrates a cost-effective and eco-friendly method for AuNP synthesis and highlights its potential in melanin-related studies and broader biomedical applications.
Keywords: Gold nanoparticles; Melanin; Green chemistry; Aronia melanocarpa; PLASMON RESONANCE; PH; BIOSYNTHESIS; DEPENDENCE; MORPHOLOGY; SURFACE; SIZE; Engineering